The Role of Sleep Quality in the Regulation of Resting Heart Rate of UPI Badminton Athletes - Muhamad Ridho Setiawan; Surdiniaty Ugelta; Tian Kurniawan (Universitas Negeri Semarang, 2026)
This study aimed to examine the relationship between sleep quality and resting heart rate among badminton athletes at the Indonesia University of Education (UPI). A quantitative correlational design was employed involving 30 active bad-minton athletes selected through total sampling; participants were required to be actively training and have competitive experience. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), while resting heart rate was measured in the morning under relaxed conditions before physical activity. Data analysis included descriptive statistics, normality testing and Pearson correla-tion. The results indicated that the athletes had an average PSQI score of 14.10, reflecting generally poor sleep quality, while the mean resting heart rate was 81.77 bpm. Normality testing showed that the data were normally distributed and suitable for parametric analysis. Pearson correlation analysis demonstrated a significant positive relationship between sleep quality and resting heart rate (r = 0.542; p = 0.002). These findings suggest that poorer sleep quality is associated with higher resting heart rates.